Estrategia metodológica lúdica espacial de adaptación para el proceso de enseñanza– aprendizaje de los niños y niñas del centro de educación inicial “corina del parral de Velasco Ibarra - Cáceres Limones, Anara Clarisa (2022)
The project arises from the observation of adaptation difficulties in students, for this reason the project's theme is a spatial playful methodological strategy of adaptation for the teaching-learning process of children in initial education, this has to be carried out carried out at the Corina Del Parral de Velasco Ibarra Initial Education Center, as a way to respond to this problem observed by teachers in the classroom, its objectives are to analyze, develop the theoretical foundation, diagnose the state, base a system of action and validate the proposal of the topic to be investigated, its methodological base is quantitative which is objective and quantifies the data, of a descriptive type, the instrument that was applied is the survey, which had ten closed-response questions, its application to The significant sample of 11 teachers from the institution in the research work allowed us to better understand the problem and thus the phenomenon studied for which a training has been designed for the teachers of the institution based on the same theme of the project, to achieve in this way address it, the objectives of the proposal are to raise awareness, inform, generate a good work environment with teachers about the subject, and create an evaluation model of the knowledge of the talks, as well as give an answer to the situation presented by the students and in this way overcome it, during the investigation there was 100% support from the teachers.